Kurasi Produk UMKM Kabupaten Probolinggo dalam Meningkatkan Daya Saing di Pasar Retail Modern - Desy Bariyyatul Qibtiyah (GUYUB: Journal of Community Engagement, 2024)
This MSMEs product curation assistance is motivated by the many potential MSMEs in Probolinggo Regency that have not been optimally developed. The purpose of this curation is to encourage MSMEs in Probolinggo Regency to compete in modern and even export markets. In addition, curating products for MSMEs can ensure that these products meet the quality and feasibility standards required by consumers. This curation assistance is a collaboration between Business Center at the University of Nurul Jadid, Rumah Kurasi, and the Probolinggo District Office of Cooperatives, Micro Enterprises, Trade and Industry. There were 20 business participants who participated in the product curation assistance. The curation process begins with product photos for digitalization needs, interviews, then giving a curation report. The curation results show that 14 MSMEs have modern market qualifications and 6 MSMEs have traditional market qualifications. The output of this curation assistance is a “Business to Business (B2B) - Business Matching” event or bringing together Probolinggo District MSMEs with buyers from shops, retail, restaurants and souvenir centers throughout Malang held at the Malang Creative Center. They will select suitable products to be sold in their stores based on the buyers' wishes and product quality standards.